Oxidative Stress Manifestation for Community-Acqiured Pneumonia in Children Living in Endemic Area of Iodine Deficiency - Pavlyshyn, Halyna; Kibar, Volha; Slyva, Viktoriia (Acta Medica, 2018)
Objective: We aimed to evaluate the state of oxidative stress, level of molecular damage in relationship with the subcellular distribution of iodine in patients with community-acquired pneumonia from the iodine deficiency region. Materials and Methods: Our study involved 70 children, 4-14 years old, with CAP (moderate severity in 35 children (Group 1); severe - in 35 (Group 2)) and 35 healthy children of the control group (Group 3). The state of organificated/inorganic, antioxidant defense system, stress-dependent systems, apoptosis and the level of molecular damage were assessed in serum samples. Results: Lower concentration of organificated iodine (12% and 59%, respectively) and high concentration of inorganic iodine (21% and 48%, respectively) were found in Groups 1 and 2. Patients of Group 2 had an inverse relationship between the levels of iodine distribution for the organic and inorganic iodine (r = - 0.645, p<0.05). In patients of Group 1, this relationship tends to decrease. The oxidative stress indicators correlated with disease severity. ROS generation indices in patients of Group 1 is 28.1 (24.2; 32.1) RFU/mg; (p < 0.05); Group 2 – 40.2 (34.2; 42.5) RFU/mg (p < 0.05); Caspase-3 is 25.77 (21.45–32.16) pmol/mg Group 1 and 39.42 (32.41–44.21) pmol/mg Group 2, (respectively, p < 0.05). We found that children with a severe pneumonia have a prooxidant activation, manifested by a significant increase of oxidation-modified proteins [2.21 (1.88–2.53) nmol/mg)] and DNA fragmentation [13.42 (10.3–15.46) %], (p < 0.05). The extent of DNA damage correlates with the extent of apoptosis. Conclusions: Increase in the concentration of inorganic iodine with a simultaneous decrease in the level of organic iodine in the blood, which leads to a more severe course of pneumonia. Fluctuations in the indices of oxidative stress, the level of molecular damage and the intensity of apoptosis in children with pneumonia correlate with the severity of the disease.